Influence of electric-hydraulic chattering on forward extrusion process. Issue 9 (February 2016) - Hu, Xinhua; Yang, Qinghua; Wang, Zhiheng; Bao, Guanjun; Hong, Xiaoxiao; Xue, Junyi
Abstract Vibration-assisted metal forming is one of the most recent and beneficial techniques used to improve material flow of the forming process. However, some technical challenges, such as the large power requirement of vibration generation and technical complexity of the metal forming process control, are difficult to solve. The main objective of this work is to investigate the possibility of applying electric-hydraulic chattering in the cold extrusion process. A series of forward cold extrusion experiments and finite element simulations were performed with and without electric-hydraulic chattering assistance. The experimental results showed that the maximum extrusion load was decreased by 5.1 % when electric-hydraulic chattering with an oil pressure of 8 MPa and a vibration frequency of 200 Hz was superimposed on the lower die. The effect of the oil pressure was more significant than the vibration frequency for the reduction of the extrusion load. A significant improvement in the surface finish of the formed parts was observed using the proposed design. The velocity of material flow during chattering extrusion process was changed cyclically, and the maximum velocity was higher than that achieved from the conventional extrusion process. The material flow at the corner area was improved. The effective stress distribution was altered periodically due to the chattering. However, the maximum effective stress was approximately equal to that attained by conventional method. Moreover, the effective strain distribution was more uniform compared to that produced by the conventional extrusion process.